Response Prediction of a TLP In Cyclonic Storm Conditions. - Higgins, Stuart; Hinwood, Jon; Thiagarajan, Krish (1997)
A six degree of freedom frequency domain model of a Tension Leg Platform (TLP), which includes the effects of non-collinear wind, wave and current, is developed to determine the response and sensitivities to environmental input. The model includes the steady forcing effects due to currents and waves, wind and wave drift. The dynamic effects include Morison type forces due to inertia and drag, spatially correlated wind and slowly varying wave drift effects. Attention is given to the position dependent mooring stiffness incorporating an iterative procedure for the determination of mean static offset position as well as the linearised mooring stiffness at the displaced location. The linearised effects of body motion, current and wave particle velocities are considered for drag determination. This model is applied to predict the response of a TLP to a sample hindcast cyclonic storm off the North West Shelf of Australia. Storm parameters used in the response model include significant wave height, spectral peak period, wave direction, storm current and direction, wind speed and direction. Results show that peak response does not necessarily coincide with the maximum sea state, but rather, different motions have different phasing with the input condition.